2012
DOI: 10.3109/00952990.2012.720320
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Concurrent Energy Drink and Alcohol Use among Socially Active Adults

Abstract: Background Research indicates that energy drink consumption and the combined use of energy drinks and alcohol are popular among young adults, although this research has typically focused on college students. Because of the potential for harms associated with this combination, it is critical to understand use among adults in nightlife scenes who may be most at risk for harms associated with combined energy drink and alcohol consumption. Objectives By focusing our sample on individuals in a range of nightlife … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
(54 reference statements)
1
23
0
Order By: Relevance
“…Other studies however, have not found significant associations between AMED consumption and problematic behaviors including binge drinking (Flotta et al, ), higher intoxication levels (Droste, Miller, Pennay, Zinkiewicz, & Lubman, ; Rossheim and Thombs, ), increased levels of sensation seeking (Snipes et al, ), being male (Malinauskas et al, ; Reid et al, ), younger age (Flotta et al, ), having a lower grade point average (Azagba et al, ; Patrick et al, ), school type (Martz et al, ), education level (Pennay et al, ), income (Pennay et al, ), general health (Pennay et al, ), sleep problems (Bonar et al, ), smoking (Pennay et al, ), and nonmedical use of opioids and anxiolytics (Khan et al, ). Further studies have also reported no significant associations between AMED consumption and drunk driving (Arria et al, ; Berger et al, ; Curtis et al, ; Flotta et al, ), wearing a seatbelt when riding in a car driven by someone else (Flotta et al, ), being hurt or injured (Berger et al, ), race or ethnic group (Patrick et al, ; Wells et al, ), sexual identity (Wells et al, ), participation in unprotected sex (Miller, ), unwanted sexual contact (Berger et al, ), and sexual victimization in women (Snipes et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies however, have not found significant associations between AMED consumption and problematic behaviors including binge drinking (Flotta et al, ), higher intoxication levels (Droste, Miller, Pennay, Zinkiewicz, & Lubman, ; Rossheim and Thombs, ), increased levels of sensation seeking (Snipes et al, ), being male (Malinauskas et al, ; Reid et al, ), younger age (Flotta et al, ), having a lower grade point average (Azagba et al, ; Patrick et al, ), school type (Martz et al, ), education level (Pennay et al, ), income (Pennay et al, ), general health (Pennay et al, ), sleep problems (Bonar et al, ), smoking (Pennay et al, ), and nonmedical use of opioids and anxiolytics (Khan et al, ). Further studies have also reported no significant associations between AMED consumption and drunk driving (Arria et al, ; Berger et al, ; Curtis et al, ; Flotta et al, ), wearing a seatbelt when riding in a car driven by someone else (Flotta et al, ), being hurt or injured (Berger et al, ), race or ethnic group (Patrick et al, ; Wells et al, ), sexual identity (Wells et al, ), participation in unprotected sex (Miller, ), unwanted sexual contact (Berger et al, ), and sexual victimization in women (Snipes et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The UPPS-P Impulsive Behavior Scale (Whiteside & Lynam, 2001; Cyders et al, 2007) is a 58- item measure of five different domains of impulsivity including sensation seeking, lacking of planning, lack of perseverance, negative urgency, positive urgency (e.g., acting rashly in a positive mood). Internal consistencies on each of the sub-scales ranged from .77 to .89.…”
Section: Methodsmentioning
confidence: 99%
“…Many college students consume energy drinks mixed with alcohol 19-32 often with the intent to consume excessive amounts of alcohol during one session. 22,25 Energy drinks consumed with alcohol result in the user feeling less intoxicated 26,33,34 although they do not lessen alcohol's effects on objective measures of impairment.…”
mentioning
confidence: 99%